If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -15 = -16 Reorder the terms: -15 + 3x = -16 Solving -15 + 3x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 3x = -16 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = -16 + 15 3x = -16 + 15 Combine like terms: -16 + 15 = -1 3x = -1 Divide each side by '3'. x = -0.3333333333 Simplifying x = -0.3333333333
| -4(n+3)=-3(n+4) | | (2a^-2b^2/10ab)^-2 | | 6c^2-8c= | | f(x)=5-6x^2 | | fA(x)=5-6x^2 | | 2x-3y-6z= | | 53=17+6c | | -6q+8=-82 | | 110=38.98+0.25x | | -2u+17=-23 | | 6=-2(10n+2) | | 5x/6-1/3=x-3/2 | | 16a^2+32ab= | | -37=-19 | | -8b+16=48 | | 13=2u+3 | | h/8-1=2 | | 32x+6= | | -7(-2v-8)=6(v+4) | | -9x+1=145 | | 8u+7=95 | | -5/7y-3=x | | q/8--40=50 | | -1/3x-3=y | | 165=g-695 | | x+y+130=0 | | y/8-26=-18 | | 6x+y=3x-2y | | 3x-3=-2(x+1)+4(2-x) | | 3x=11/6 | | 32=2y-7 | | -23=r/-11 |